Poor Slaughterhouse Waste Management: Empirical Evidences From Nigeria And Implications On Achieving Millennium Development Goals . (2014)
Adequate knowledge and practice of waste management among slaughterhouse workers can help limit the associated effects of poor disposal on access to safe water, environmental sustainability and quality of life which are core areas of Millennium Development Goals (MDGs). Data on knowledge, attitudes and practices of waste management of 390 randomly selected slaughterhouse workers in Nigeria were collected and analyzed using multiple regression statistics. The results reveal that the majority of the respondents had poor attitudes (75.6%) and practices (97.4%) of proper waste management, though 51.5% demonstrated good knowledge. While 51.3% knew that slaughterhouse wastes are related to diseases, 75.4% were unconcerned that poor management could be major public health and environmental hazards and 74.4% discharged slaughterhouse wastewater into surrounding streams. Gender, education and work experience were significantly associated with good knowledge (p <0.05). These poor attitudes and practices have negative implications on environmental health conditions, access to safe water and quality of life. Therefore, addressing poor slaughterhouse waste management issues in developing countries becomes imperative to making achieving the MDGs a reality.